Enhanced biomedical potential of polyurethane/hydroxyapatite composites through chemical modification: A comprehensive study on structure, morphology, and cytocompatibility for tissue regeneration - Sultan Misbah; Parveen Shaista; Uddin Mohammad N.; Jubeen Farhat; Kazi Mohsin (Acta Pharmaceutica)
Polyurethane/hydroxyapatite (PU/HA) composites are well-known for various biomedical applications. This study reports a chemical approach to improve the interaction between HA and PU matrix. HA was surface-modified with 1,6-hexamethylene diisocyanate (HMDI). First, an isocyanate-modified HA (IHA) was synthesized by hydro-thermal method. Second, IHA was incorporated into a separately synthesized thermoplastic PU by a solvent casting technique. A series of PU/IHA composites was prepared by varying PU᾿s soft and hard segments. The IHA was added to PU (5 and 10 %). The FTIR spectra exhibited characteristic bands of urethane and HA, confirming the synthesis of the composites. XRD study showed the crystallite size of IHA (20 Å) with hexagonal geometry and an amorphous to semicrystalline nature of composites. SEM showed that composites displayed porous and granular morphology. The TGA thermograms of the composites revealed the thermal stability up to 400 °C. The IHA addition considerably improved hydrophilicity and degradation of the composites in simulated body fluid (SBF). MTT assay revealed improved cytocompatibility (> 80 %) of the composites. These results demonstrated an appreciable improvement in structure, morphology, hydrophilicity, degradation, and cytocompatibility of PU/IHA composites by chemical modification of HA. Hence, these composites possess remarkable potential for biomedical applications such as tissue regeneration.